2017
DOI: 10.14254/2071-789x.2017/10-4/14
|View full text |Cite
|
Sign up to set email alerts
|

Reengineering of Electricity Market Monitoring

Abstract: ABSTRACT. The main goal of this paper is to present new indices and a new structure of the electricity market monitoring system. The proposed structure, along with the analytical methods and indices applied to this structure, could be used from the viewpoint of both market operator and market participants. This paper also describes, in a rather simplified manner, the algorithms of market monitoring on the case study of Spanish electricity market.JEL Classification: Q4, E03, E37, O10, N70

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…The electricity consumption on the demand side will be affected by the operation mechanisms of the electricity market [48], and the electricity price purchased from the external grid in this paper is based on the time-of-day tariff scheme [49]. The peak periods are 8:00-11:00 and 18:00-23:00, and the electricity price is 1.35 CNY/kW•h.…”
Section: Case Study and Resultsmentioning
confidence: 99%
“…The electricity consumption on the demand side will be affected by the operation mechanisms of the electricity market [48], and the electricity price purchased from the external grid in this paper is based on the time-of-day tariff scheme [49]. The peak periods are 8:00-11:00 and 18:00-23:00, and the electricity price is 1.35 CNY/kW•h.…”
Section: Case Study and Resultsmentioning
confidence: 99%
“…Kayhan S. et al, (2010) confirmed this type of causality between electricity consumption and economic growth for Romania during 2001-2010. This type of Granger causality is typical for the EU, because for other parts of the world showed that high GDP rates allow for more electricity consumption Karanfil & Li, 2015;Kasperowicz et al, 2017;Pinczynski & Kasperowicz, 2017).…”
Section: Source: Authors' Own Computationsmentioning
confidence: 88%
“…Mini-grids today include various AC [135] and DC [136,137] transmission options and a variety of primary energy sources (oil, biomass, hydro, wind, solar, hydrogen, or hybrids among others) [27,138]. Monitoring systems [139] allow companies to gather a large amount of data on systems usage, enabling them to refine their business models and technical solutions. Finally, smart grids with improved automation and communication between supply and demand side technologies have enhance their effectiveness [140].…”
Section: Discussionmentioning
confidence: 99%